Literature as utopia : between Jacques Derrida and Ingeborg Bachmann - Deotto, Francesco (Sapere Aude, 2013)
While Derrida admitted the “critical powers” of utopia, he was generally wary of the term and used it only very rarely. He was particularly concerned that it “can be too easily associated with dreams or demobilization”. By referring to the notion of utopia as proposed by Ingeborg Bachmann, which, from our point of view, overcomes the general concerns expressed by Derrida, this paper reconsiders the relationship between his philosophy and the utopian tradition. On the one hand, we suggest that the utopian perspective can not only be applied to certain political concepts (such as the idea of “democracy to come” or the idea of “unconditional hospitality”), but also to the concept of writing itself, which Derrida analysed in De la Grammatologie (1967) and in his Introduction (1962) to Husserl’s Origin of Geometry. On the other hand, we draw some important analogies between Derrida’s conception of literature and the idea of “literature as utopia”, as discussed by Bachmann in a conference bearing that name in 1960. Embora Derrida admitisse os "poderes críticos" da utopia, ele geralmente era cauteloso com o termo e o utilizava apenas muito raramente. Preocupava-se particularmente com o fato de que o termo "pode ser muito facilmente associado a sonhos ou desmobilização". Ao se referir à noção de utopia como proposta por Ingeborg Bachmann, que, de nosso ponto de vista, supera as preocupações gerais expressas por Derrida, esse artigo reconsidera a relação entre sua filosofia e a tradição utópica. Por um lado, sugerimos que a perspectiva utópica não apenas pode ser aplica a certos conceitos políticos (como a ideia da "democracia porvir" ou a ideia de "hospitalidade incondicional"), mas também ao conceito da própria escrita, que Derrida analisou em De la Grammatologie (1967) e em sua Introduction (1962) à Origem da Geometria de Husserl. Por outro lado, traçamos algumas importantes analogias entre a concepção de literatura de Derrida e a ideia de "literatura como utopia", como discutida por Bachmann em uma conferência com o mesmo nome em 1960.